STUDENT’S PERCEPTION TOWARDS THE IMPLEMENTATION OF YOUTUBE SONG VIDEO CONTENT FOR LEARNING ENGLISH SONG LYRIC - Ichda Sholikhatun Nisa; Khoirul Anwar; Paulina Paulina (DIDAKTIKA, 2019)
Student’s Perception is the process of students to interpret and organize an environment into meaningful information which cover student’s feeling of like or dislike towards something, it includes positive and negative opinion. Student’s Perception in this study focuses on the implementation of YouTube in Learning English song lyric. This study uses mixed method design. 72 students in class XI Science 3 and 7 in SMAN 1 Cerme become the subject of this study. The data was collected using Perception Questionnaire. After grained the data, the writer analyzed by using some formulas and SPSS 1.16. The writer also used interview to ensure the result of questionnaire.Based on the data analysis that was collected and analyzed from the students of XI-Science 3 and 7, 58,3 % of the students had positive perception towards the implementation of YouTube in Learning English song lyrics, from the interview and questionnaire result, this study is also gave many advantages from the student’s perception, the writer would like to answer the research questions as stated before. It consisted of a question involving to find out the research question “What is the students’ perception on the implementation of English song video in YouTube for learning song lyric at eleventh grade students in SMA Negeri 1 Cerme?”. The result is students had good perception, the students gave positive respond in every activity conducted in the classroom because the song make the class become more conducive, fun, and meaningful, so it influenced their ability in listening improved well. Not only that, they also mastered the component of language in English, such as grammar, vocabulary, and pronunciation. The result of questionnaire and interview, the percentage from students who disagree that learning English song lyric improved their understanding in identifying grammatical structure. Even though they have learnt grammar for many times, but they still have difficulties in learning grammatical structure. Not only that, students also have difficulties in differentiating the native speaker accent, such as American accent and British accent. Students also weak in imitating the sound of speech. It is because the native speaker speaks fast, so that they cannot get the word easily, they still repeat the English song again and again. Teacher also uses group discussion technique in learning English song lyric from YouTube, it made the students become more active in communicate and share ideas with their friends.